Teachers' teaching strategies in a sample of South African inclusive classrooms - Lake, Nicola (My University, 2016)
The study explored how teachers in mainstream schools in South Africa attempt to ensure all learners are included in the classroom as active participants. Inclusive education has been the educational policy in South Africa since 2001 and teachers are invaluable in implementing it, thus this research explored what teachers do in the classroom to ensure all learners are included as active participants. In particular the study explored whether teachers use learner-centred and differentiated instruction, strategies recommended for the inclusive classroom. Barriers and differences among learners that teachers consider in ensuring inclusion of learners in the curriculum and classroom as well as factors that hamper their ability in ensuring inclusion of learners were also explored. The sample of the study consisted of 14 teachers from four primary schools in the Johannesburg East region. Three focus groups and one individual interview were conducted. Questions looked at teaching strategies teachers use in their inclusive classrooms, factors among learners they consider in creating inclusive lessons and factors that hamper their implementation of inclusive education. It was found that teachers view learner-centred and differentiated instruction as useful within the inclusive classroom and they indicated that they do use these strategies. However, teachers indicated that they have received insufficient pre and in-service training for such strategies and for inclusive education in general and that there is thus a need to improve pre and in-service training for inclusive education. Moreover, commonly occurring factors such as large classes, limited resources, heavy workload, insufficient support services and time constraints were argued to make such strategies difficult to use. In discussing differences among learners considered in creating inclusive lessons teachers focused on cognitive and academic differences, while differences in culture, learning styles, interests, personality and socio-economic background were discussed infrequently. Barriers that teachers discussed as important to accommodate for in the inclusive classroom included hearing, visual and emotional barriers and poor concentration. Language was also identified as an important barrier to accommodate for. The family were identified as an important resource in achieving the goals of inclusive education, however it was indicated that there is a lack of family involvement. Limitations of the study are also discussed as well as directions for future research.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Psychology by coursework and research report in the faculty of Humanities, University of the Witwatersrand, Johannesburg, 2010
Keywords: Inclusive education--South Africa; Special education--South Africa; Children with disabilities--Education--South Africa; Teaching--Social aspects--South Africa